2008
DOI: 10.1055/s-2008-1040283
|View full text |Cite
|
Sign up to set email alerts
|

Das Styloid-Syndrom

Abstract: Elongated Styloid Process Syndrome requires its consideration in differential diagnosis of degenerative disease of the cervical spine. Radiating pain on certain movements of the cervical spine is a symptom of an elongated styloid process as well. First basic anatomy and pathology, symptoms and differential diagnosis of the elongated styloid syndrome are discussed. A case history is presented together with X-rays of the cervical spine and images of three dimensional CT-reconstruction to show the full length of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…3D-CT images reformatted from the raw data obtained with a spiral scanner provide the necessary information on the styloid process, including its length, direction, and anatomical relation to adjacent tissues. Previous studies reported that 3D-CT is reliable for measurement of the actual length of the styloid process and the stylohyoid ligament [9-11], and helpful in establishing the diagnosis of Eagle's syndrome. In addition, 3D-CT helps the patient understand the abnormality and planned treatment.…”
Section: Discussionmentioning
confidence: 99%
“…3D-CT images reformatted from the raw data obtained with a spiral scanner provide the necessary information on the styloid process, including its length, direction, and anatomical relation to adjacent tissues. Previous studies reported that 3D-CT is reliable for measurement of the actual length of the styloid process and the stylohyoid ligament [9-11], and helpful in establishing the diagnosis of Eagle's syndrome. In addition, 3D-CT helps the patient understand the abnormality and planned treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Dans la série de Wada et al [29], le scanner avait une utilité certaine dans le diagnostic de la maladie. D'autres auteurs comme Hass et al [30] et Bafaqeeh et al [31] ont rapporté la fiabilité dans la mesure de processus styloïde et du ligament stylo-hyoïdien lorsqu'ils utilisaient les reconstructions 3D MPR (multiplanar reconstruction) et VRT (volume rendering technique).…”
Section: 22unclassified